Penerapan Program Dinamik dalam Menentukan Rute Optimal Perjalanan dari Pematangsiantar Menuju Samosir - Linda Puspa Ayu Simarmata; Intan Sitanggang; Mira Andini; Barthy Ladi C. Sirait (Journal of Information System Research (JOSH), 2025)
A tourist area with many roads often makes it difficult for someone to determine the optimal route, both in terms of distance or costs incurred from the place of origin to the destination. Moreover, in determining a decision support system to determine the route of a tourist trip is needed to determine the optimal route so that the costs incurred are minimum. To solve the problem in this article, we use the dynamic programming method where the method used is the forward method. With the aim of determining the fastest distance from Siantar to Samosir so that the minimum costs incurred. Dynamic Program (dynamic programming) is a method of solving problems by decomposing the solution into a set (stage), such that the solution to the problem can be viewed as a series of interrelated decisions. The solution used is dynamic programming with the data that has been obtained then processed and calculated so that the results obtained are optimal, It is known from the results of the calculation analysis, it can be concluded that the shortest route for tourist trips from Siantar to Samosir, namely from Siantar then to Sidamanik, then to Tomok, continuing to Simanindo, then to Pangururan until finally to Tele with a distance of about 116,2 km /h.